Citra Penjajahan Jepang di Indonesia yang Terpantul dalam Beberapa Novel Pramoedya - Hun, Koh Young (Wacana, Journal of the Humanities of Indonesia, 2006)
Images of Japanese troops which drawn by Pramoedya in his works indeed related with his own experiences. Pramoedya through his characters portrays his view on humanities. Pramoedya depicted the brutality of Japanese troops in their occupation in Indonesia. All Japanese propaganda delivered false messages and caused disasters for Indonesian people. Japanese culture retardation and their brutality made the author suffer and down. Even though his novels associate with anti Japanese occupation and patriotism among the youth, humanities issues in fact appear as a strong theme in all his works.